2021
DOI: 10.1242/dev.199511
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila ribosome protein S5 paralog RpS5b promotes germ cell and follicle cell differentiation during oogenesis

Abstract: Emerging evidence suggests that ribosome heterogeneity may have important functional consequences in the translation of specific mRNAs within different cell types and under various conditions. Ribosome heterogeneity comes in many forms including post-translational modification of ribosome proteins (RPs), absence of specific RPs, and inclusion of different RP paralogs. The Drosophila genome encodes two RpS5 paralogs, RpS5a and RpS5b. While RpS5a is ubiquitously expressed, RpS5b exhibits enriched expression in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…Intriguingly, mESCs display different ribosome subunit stoichiometries in monosomes and polysomes, and these associate with different mRNAs ( Shi et al, 2017 ). Recent work in the Drosophila germline has shown that a paralogue of RpS5 is required for normal progression of differentiation and preferentially promotes translation of a subset of transcripts ( Kong et al, 2019 ; Jang et al, 2021 ). These tantalizing observations raise the possibility that different incorporation of ribosomal subunits into ribosomes may regulate stem cell behavior; however, this has not yet been demonstrated.…”
Section: From Global Translational Control To Specific Protein Expres...mentioning
confidence: 99%
“…Intriguingly, mESCs display different ribosome subunit stoichiometries in monosomes and polysomes, and these associate with different mRNAs ( Shi et al, 2017 ). Recent work in the Drosophila germline has shown that a paralogue of RpS5 is required for normal progression of differentiation and preferentially promotes translation of a subset of transcripts ( Kong et al, 2019 ; Jang et al, 2021 ). These tantalizing observations raise the possibility that different incorporation of ribosomal subunits into ribosomes may regulate stem cell behavior; however, this has not yet been demonstrated.…”
Section: From Global Translational Control To Specific Protein Expres...mentioning
confidence: 99%
“…In addition, loss of Nop10 and Nop60B resulted in cysts with hypertrophic nucleoli compared to wild-type cysts, suggesting a ribosome biogenesis defect ( Figure S5C-S5F ) (Neumüller et al, 2008; Sanchez et al, 2016). To verify that the H/ACA box deposits pseudouridine on rRNA during oogenesis, we co-immunopurified the 40S and 60S ribosomal subunits from the germline, utilizing a germline-enriched HA-tagged ribosomal protein RpS5b ( Figure S5G-S5I ) (Jang et al, 2021) (Chen and Dickman, 2017). Mass spectrometry analysis showed that loss of the H/ACA box member Nop10 led to a significant decrease of pseudouridine on rRNA relative to controls ( Figure 3A, Supplemental Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis predicts that compromised ribosome biogenesis will phenocopy loss of H/ACA box components. We impaired ribosome biogenesis by depleting ribosomal protein paralogs RpS10b and RpS19b in the germline, as the depletion of other ribosomal proteins that do not have paralogs results in GSC differentiation defects or loss of cyst stages that would mask the cyst differentiation block (Jang et al, 2021; Martin et al, 2021; McCarthy et al, 2022; Sanchez et al, 2016). Depletion of RpS10b and RpS19b phenocopied loss of H/ACA box components, leading to a block in cyst differentiation and decreased levels of Rbfox1 and Bru1 proteins without a concomitant loss of their mRNAs ( Figure S7A-S7K, S8A-S8H ).…”
Section: Resultsmentioning
confidence: 99%
“…Above, we speculated that variants in IQCN may disturb the function of IFT‐related proteins via calmodulin regulation, and found that ribosomal protein family members are downregulated under IQCN knockout. A previous study suggested that ribosomal protein loss is associated with microtubule‐based defects (Jang et al , 2021 ); however, the exact regulatory mechanism and the role in spermiogenesis require further investigation.…”
Section: Discussionmentioning
confidence: 99%